Anticancer drug delivery systems based on specific interactions between albumin and polyglycerol. Issue 14 (27th January 2016) - Beiranvand, Zahra; Bani, Farhad; Kakanejadifard, Ali; Laurini, Erik; Fermeglia, Maurizio; Pricl, Sabrina; Adeli, Mohsen
Abstract : Since albumin is the main transporter and the most abundant protein in the blood, interactions between this protein and drug/gene nanocarriers are of great importance to ensure successful delivery to target tissue(s) in the body. Abstract : Here, we report for the first time a facile method for the preparation of novel drug delivery systems based on supramolecular interactions between β-cyclodextrin-polyglycerol conjugates (β-CD- g -PG) and human serum albumin (HSA). The results obtained by combined experimental/modeling studies showed that the main drivers to the formation of HSA/β-CD- g -PG supramolecular entities are host–guest interactions between β-CD- g -PG and the aromatic side-chains of HSA residues. Due to these interactions, HSA undergoes a confined yet fundamental conformational transition, leading to greater exposure of the hydrophobic protein domains available to hydrophobic drug binding. Next, the binding affinity and loading capacity of the HSA/β-CD- g -PG supramolecular nanovector for doxorubicin (DOX) and paclitaxel (PTX) were investigated. Both drug/HSA binding constants ( K b, HSA/DOX = 3.24 × 10 3 M −1 and K b, HSA/PTX = 5.65 × 10 1 M −1 ) sensibly increased in the presence of β-CD- g -PG ( K b, HSA/β-CD- g -PG/DOX = 2.78 × 10 4 M −1 and K b, HSA/β-CD- g -PG/PTX = 2.82 × 10 2 M −1 ). In line, both protein drug loadings increased by about 20% upon HSA/β-CD- g -PG interaction (80% and 71% for DOX and PTX, respectively) with respect to the loading capacity of the bare HSA (60% and 50%). Due to the improved loading capacity with minimal changes in the structure of HSA, this system is a promising vector for future cancer therapy.